Barbara Krauz-Mozer, Piotr Borowiec, Paweł Ścigaj, Kim jesteś politologu? Historia i stan dyscypliny w Polsce (K. B. Janowski) - Janowski, Karol B. (Przegląd Politologiczny, 2018)
Barbara Krauz-Mozer, Piotr Borowiec, Paweł Ścigaj, Kim jesteś politologu? Historia i stan dyscypliny w Polsce (K. B. Janowski)